THE WHAT AND HOW ARE INDEPENDENT WRITING STRATEGIES IN ENGLISH DEPARTMENT STUDENTS: A SURVEY STUDY - Sitompul, Siti Kholija (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
As nurturing efficient classroom practice is always the teachers’ goal in language learning-teaching, learning strategies are provided for students. In this present study, independent writing activities are addressed to English Department students to enable them to perform writing skills as being independent is the final goal of writing skills. This study was conducted through a survey involving 33 students from a state university in Malang, aiming at exploring the students’ independent strategies in writing skills. This study employed two instruments consisting of a closed-ended questionnaire comprising 22 questions and a semi-structured interview comprising three questions, respectively. The students involved in the interview were three students, and the subjects were saturated since their responses were almost the same. The instruments were analysed quantitatively and qualitatively to find the percentages of the strategies in use and the deep students’ responses using thematic analysis. Using the instruments, this present study reported that the students employed three strategies: pre-writing, writing, and revising. The students confirmed that three strategies were undergone in pre-writing, comprising resourcing, outlining, and elaborating. The second strategy, writing, referred to re-reading the writing plans and the draft composed during writing occurred. The last strategy was revising, as students underwent both re-arranging and re-concepting after self-checking their writing products. Therefore, the study affirmed that the employed strategies benefit the students in coping with the complexity of writing skills. Finally, the study will theoretically document the students’ strategies in initial planning until composing texts. Therefore, the study recommended further studies to gradually and deeply investigate the students’ writing strategies in independent settings to uncover to what extent the writing strategies were well passed by the students.